RISE: Nextgreen Global - UiTM research collaboration / Assoc. Prof. Dr Siti Noor Hajjar Md Latip - Md Latip, Siti Noor Hajjar (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Nectgreen Global is one of the leading printing companies in Malaysia and the first magazine and book printing company to be public-listed on the Kuala Lumpur stock exchange.